Conventional Complete Denture in Patients with Ectodermal Dysplasia. (6th September 2015) - Vilanova, Larissa Soares Reis; Sánchez-Ayala, Alfonso; Ribeiro, Giselle Rodrigues; Campos, Camila Heitor; Farias-Neto, Arcelino
Abstract : Ectodermal dysplasia is described as heritable conditions that involve anomalies of structures derived from the ectoderm, including hypodontia. In the cases of edentulous young patients, who did not finish their craniofacial growth, treatment with conventional complete denture is a suitable alternative. The aim of this study was to report a case of mandibular edentulism treated with conventional complete denture in a thirteen-year-old patient diagnosed with hidrotic ectodermal dysplasia. Typical features, such as frontal bossing, depressed nasal bridge, protuberant lips, scarce hair, and brittle nails, were visualized during the extraoral examination. The intraoral inspection and radiographic analysis revealed oligodontia, dental malformation, and prolonged retention of deciduous teeth at maxilla and total edentulism at mandible. A conventional complete denture was planned and constructed following the same steps of technique as recommended in adults. Although this option is not a definitive treatment, the patient and his parents were satisfied with his improvement in chewing and speech, as well as with the aesthetic benefits.